Structure Analysis of Amorphous and Liquid Magnesium Silicate - Thi Lan, Mai; Thi Thao, Nguyen (VNU Journal of Science: Mathematics - Physics, 2021)
We use the Oganov potentials and period boundary condition to perform molecular dynamics simulation of amorphous and liquid Mg2SiO4 systems under pressures 0 GPa and 40 GPa. We clarify structure of amorphous Mg2SiO4 at 0 and 40 GPa and compared with the one of Mg2SiO4 at liquid state. Especially, the origin of sub-peaks in radial distribution function of O-O, Si-Si and Mg-Mg pairs is explained clearly. The change of radial distribution functions, coordination number and the number of all types of bonds including the corner-, edge- and face-sharing bonds is also discussed in detail in this paper.